Differences Related to Zakat Between the Islamic System and the Pakistani Legal System - Rasham Armab Saikhu (Law and Policy Review, 2025)
This research deals with the study of Zakat in the Islamic system and in the Pakistani legal system. It comparatively analyses both these systems to highlight the main differences between them. In doing so, initially, it discusses the basic principles of Zakat in Islam, such as nisab (minimum wealth) and the rate of Zakat on different items, its religious and economic importance, as well as its exemptions. Later on, its legal development in the Pakistani legal system will be discussed. That legal development is related to the period before and after the formation of the Zakat and Ushr Ordinance 1980. Finally, the differences between these systems are being discussed to amend the Pakistani laws to make them consistent with Islamic law